The role of adiponectin in human vascular physiology - Vaiopoulos, A; Marinou, K; Christodoulides, C; Koutsilieris, M (2012)
Adiponectin (ApN) is an adipose tissue-derived hormone which is involved in a wide variety of physiological processes including energy metabolism, inflammation, and vascular physiology via actions on a broad spectrum of target organs including liver, skeletal muscle, and vascular endothelium. Besides possessing insulin sensitizing and anti-inflammatory properties ApN also exerts a pivotal role in vascular protection through activation of multiple intracellular signaling cascades. Enhancement of nitric oxide generation and attenuation of reactive oxygen species production in endothelial cells along with reduced vascular smooth muscle cell proliferation and migration constitute some of ApN's vasoprotective actions. Additionally, recent data indicate that ApN has direct myocardio-protective effects. Decreased plasma ApN levels are implicated in the pathogenesis of the metabolic syndrome and atherosclerosis and may serve as a diagnostic and prognostic biomarker as well as a rational pharmaco-therapeutic target to treat these disorders. This review article summarizes recent work on the cardiovascular actions of ApN. © 2011 Elsevier Ireland Ltd. All rights reserved.